Kinerja Pegawai Dinas Pangan Kota Bandar Lampung: Perspektif Teori Resource-Based View - Sahril Iskandar; Khairudin Khairudin (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
Employee performance1is an important aspect in the success of public sector organizations, particularly in improving1the quality of service to the community. This study discusses the role of work motivation and employee competence as internal factors that are1thought to influence employee performance at the Bandar Lampung City Food Agency. The research problem1focuses on the question of whether work1motivation and employee competence affect employee1performance, either partially or simultaneously. The novelty of this study1lies in the use of the Resource-Based View (RBV). This study uses a quantitative approach towards employees of the Bandar Lampung City Food Service. The results1show that1work motivation has a positive1and significant effect on employee performance, while employee competence has a positive but insignificant effect. Simultaneously, work motivation and competence have a significant effect on employee performance. This study concludes that improving employee performance is more determined by strengthening work motivation, while competence needs to be managed in an integrated manner in order to contribute to more optimal and sustainable performance.